HUBUNGAN TINGKAT KECEMASAN SISWA DALAM MENGHADAPI TES DENGAN TINGKAT MOTIVASI BELAJAR BIOLOGI PADA SISWA KELAS X MIA SMA NEGERI 21 JAKARTA - Eka Putri Azrai; Dian Evriyani; Achmad Ramadani Prastya (Universitas Negeri Jakarta, 2016)
Test is an activity used as indicators success of education that applies to all subjects including biology. Unfortunately, there are assumption that biology is a boring subject , too much memorizing, and that is not relevant for our life. It can increase the anxiety experienced by students during the tested. This study aimed to determine the relationship between test anxiety level and Learning Biology Motivation. This study was conducted in 21 Senior High School Jakarta on January until February 2016. Research method used in this study was correlational study. Population from this study were X MIA students. A total of 122 students used for this study were taken by Simple Random Sampling. Prerequisites tests data was homogeneous and normally distributed. Correlation test resulted -0,398 which means there was a relationship between test anxiety level with biology learning motivation level on X MIA Students 21 Senior High School Jakarta. Regulation test resulted Å¶ = 85.725 - 0.312x, with X is test anxiety level and Y is biology learning motivation level. Determination coefficients resulted 0.159 that mean test anxiety have a contribution 15.9% determined learning motivation, while the other factor have a contribution too.